Pengaruh Penerapan Standar Akuntansi Pemerintahan, Kualitas Sumber Daya Manusia, Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Bungo - Rizkiyah Lestari Utami; Yudi -; Misni Erwati (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
This study aims to see the effect of implementing government accounting standards, the quality of human resources, internal control systems on the quality of local government financial reports. This type of research includes causal associative research (cause and effect). The population in this study is the OPD in Bungo Regency, namely a total of 23 OPD consisting of the Office, Agency, Regional Secretariat and District. The number of respondents each consisted of one PPK person and one expenditure treasurer, with a total of 46 respondents. The sample in this study used a saturated sampling technique. The type of data used is primary data. The analysis was performed using a multiple regression model. The results of this study indicate that the application of government accounting standards and internal control systems has a significant positive effect on the quality of local government financial reports (sig 0.000). The quality of human resources has no effect on the quality of local government financial reports.